Minding minds : evolving a reflexive mind by interpreting others - Bogdan, Radu J. (Cambridge, Mass. : MIT Press, 2000)
Drawing on philosophical, psychological, and evolutionary perspectives, Bogdan analyzes how primates create the resources for ""metamentation""â__the ability of the mind to think about its own thoughts.
1. Tales of many minds -- 2. Minding others -- 3. Unique development, unique mind -- 4. The reflexive mind -- 5. Situated minding -- 6. Unsituated metaminding -- 7. Mind unification -- 8. Parting thoughts.
"A Bradford book."
Includes bibliographical references (pages 199-212) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Philosophy of mind; Self-knowledge, Theory of; Other minds (Theory of knowledge); Metacognition; Other (Philosophy); Philosophie de l'esprit.; Connaissance de soi; Altérité.; Métacognition.; PHILOSOPHY -- Mind & Body; Other (Philosophy); Metacognition; Other minds (Theory of knowledge); Philosophy of mind; Self-knowledge, Theory of; Metacognitie; Reflexiviteit; Primaten; Mensen; Evolutie